Pengujian Rasio Kinerja Instalasi Panel Surya Tipe Silikon–Kristal pada Kondisi Cuaca Kota Malang - Asrori Asrori; Imam Mashudi; Suyanta Suyanta (Polinema Press, Politeknik Negeri Malang, 2019)
Indonesia has the potential of global solar radiation reaching 4.5 to 5.5 kWh /m2/day. Due to this fact, the utilization of solar energy using solar panel technology is an alternative to use energy from renewable resources. In the present study, the performance of crystalline silicon solar panels (mono and polycrystalline) under malang city climate (7,944o S ;112,613o E) were experimentally compared. The solar radiation, ambient temperature, current and voltage output, were monitored to determine normalized power output efficiency and the performance ratio of the two different solar panels. The obtained results indicate that the performance of solar panel is influenced by solar radiation, weather condition (cloudy and clear day), wind velocity and type of solar panel installation. Finaly, the normalized power output efficiency of the mono and polycrystalline by 70.79% and 66.33%, respectively. In addition, the performance ratio of mono and polycrystalline by 0.63 and 0.61, respectively. Its showed that, the performance of mon